IMPRESSIONS OF AN ENGLISH TRAVELLER IN LIBYA - Toynbee , Arnold (مجلة كلية الاداب, 1969)
I first became acquainted with Libya more than seventy years ago, when I was a child in London before the close of the nine teenth century. Someone gave me an annual volume of an Ame rican children's magazine, and the part of its contents that attrac ted me most was a serial story - part fiction, part fact - of the war of 1801-4 between the United States and the Turkish governor of Tarabolous. This war did not involve either the Ottoman Empire or the people of Tripolitania. The governor of Tripoli was at that time virtually independent, and he was also an autocrat. His sub jects were not consulted. However, this story did at least teach me, at the age of seven or eight, the position of Libya on the map of -the World. Libya impinged on me more forcibly in the autumn of 1911. I was on my way through France and Italy to Greece when the Italian Government declared war on the Ottoman Empire and invaded Libya. By that date, the Ottoman Imperial Government was once again in effective control of Libya, and the Turks joined forces with a Libyan national resistance movement. In that war the Libyans had the beau role; they were gallantly defending their country .against an unprovoked act of aggression by a stronger power. On the Italian side, it was not a people's war. I remember watching Italian conscripts embarking at the port of Civita Vecchia for the Libyan front. They looked unenthusiastic and indeed positively unhappy.